A social-ecological investigation into urban domestic gardens and avifauna in medium-sized towns of the Eastern Cape, South Africa - Tricam, Shayla (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
Urban domestic gardens are an often overlooked component of urban green infrastructure, despite their potential to contribute to the preservation of urban biodiversity. As opposed to public greenspaces, private gardens are individually owned and managed, thus act as social-ecological systems, where the cumulative actions of urban residents can scale up to influence ecological patterns and processes on a larger scale. The diversity of fauna and flora within urban gardens provide a range of ecosystem goods and services, as well as less tangible benefits in the form of recreation, education and culture. However, little is known about the contribution of urban domestic gardens to urban biodiversity and its potential conservation value in South Africa. This study investigated urban domestic gardens along a socio-economic gradient in two medium-sized towns, Grahamstown and Port Alfred in the Eastern Cape, South Africa. This study found distinct differences among urban resident garden management practices as well as the avifauna which were seen within the gardens across the socio-economic gradient. The Garden Management Intensity index was higher within affluent households compared to other socio-economic levels, with subsequent management scores not differing statistically along the gradient. While there was variation within garden management practices, as well as the number of residents who participated in supplementary bird feeding, little variation was seen in the activities which were enjoyed by the residents, indicating numerous benefits the garden environment provides for all urban residents. The bird community composition along the socio-economic gradient displayed patterns directly reflecting the "luxury effect" , where households with a higher socio-economic status had harbour gardens with greater levels of biodiversity. This study showed that affluent gardens displayed far greater diversity, richness and abundance of urban birds. Multivariate analyses confirmed the patterns by highlighting a distinct bird community in the affluent zone, compared to other two socio-economic zones, which housed a second bird community. Furthermore, the main driver of the bird community composition was dominated by vegetation complexity, most notably tree cover within the gardens. Therefore, this study highlighted that patterns of ecological inequality are highly evident in medium-sized towns in South Africa, where older, affluent suburbs households display greater diversity and abundance of birdlife, compared to subsequent socio-economic zones within the study. Prioritisation with regards to the benefits a garden environment brings to urban residents in terms of a connection to nature, access to urban greenery, and relationship to urban wildlife is vital and should be promoted and planned for across all socio-economic zones.
Keywords: Urban ecology (Biology) -- South Africa; Biotic communites -- South Africa; Gardens -- South Africa -- Managemenet; Birds -- Ecology -- South Africa; Gardening to attract birds -- South Africa